Study on large deformation and failure mechanism of deep buried stratified slate tunnel and control strategy of high constant resistance anchor cable. (February 2023) - Sun, Xiaoming; Jiang, Ming; Miao, Chengyu; Wang, Jian; Zhang, Jiaxuan
Highlights: The deformation and failure mechanism of deep buried horizontal layered soft rock tunnel is studied through physical model experiment. Horizontal stress has significant influence on the deformation of surrounding rock of horizontal layered tunnel. The failure process of tunnel is accompanied by abnormal temperature changes. A new support scheme of long and short high constant resistance anchor cable is proposed. The new support scheme can effectively control the deformation of tunnel surrounding rock. Abstract: Aiming at the significant deformation problem of deep buried stratified soft rock tunnel, taking the No.3 inclined shaft of Muzhailing tunnel as background, the deformation and failure mechanism of the tunnel and the control strategy of high constant resistance anchor cable are studied. The deformation and failure mechanism of stratified tunnel surrounding rock is studied by physical model test, including the tunnel's temperature field, strain field, and displacement field from excavation to failure. Lateral stress significantly influences the deformation of the surrounding rock of the horizontal stratified tunnel. The surrounding rock of the tunnel forms a dumbbell-shaped tensile stress zone under the action of stress. The high tensile stress of the roof and floor leads to dislocation and layer separation, which causes floor heave failure and temperature change. The indoor tensile test verified the super strength characteristics and large deformation of the high constant resistance anchor cable. Based on the excavation compensation method and the coupling control mechanism of high constant resistance long and short anchor cables, a new high prestress constant resistance coupling control strategy is proposed. The numerical simulation and field test studies according to the new design are presented, which show that the high constant resistance anchor cable coupling support significantly reduces the tensile stress zone, effectively controls the deformation of tunnel surrounding rock, and avoids the damage of supporting structure and the cracking and deformation of the lining. The research results can provide a reference for constructing and supporting deep-buried, stratified soft rock tunnels.